Coupled hydraulic behavior of confluence and diversion flow with multi-gate regulation in a hydropower expansion project - Jing Tian; Shiya Guo; Peng Xu; Yu Wang (PLoS ONE, 2025)
Confluence and diversion flows are common yet complex three-dimensional hydraulic phenomena, and understanding their behavior is crucial for the safe and efficient operation of hydraulic structures, especially when they occur in close proximity within the same project. This study investigated the hydraulic interactions between the culvert intersection and the regulating and diversion gates of a hydropower station expansion using a 1:30 scale physical hydraulic model (Froude similarity). Practical operational strategies for the gates were developed to meet diversion flow requirements under normal conditions. Results indicate that, under typical operational and maintenance scenarios, the Froude number (Fr) between the culvert intersection and the regulating gate ranges from 0.03 to 0.26, indicating that the flow remains subcritical throughout this section. The water level at the Phase I culvert outlet is primarily governed by the total discharge from the Phase I and Phase II culverts, with flow distribution between them has a secondary effect. The stable water level upstream of the regulating gate is minimally influenced by the culvert flow distribution. Moreover, the converging flow has a limited impact on diverging flow at the regulating and diversion gates. The diversion flow rate of the diversion gate remains largely unaffected by the regulating gate’s operation, confirming the proposed gate operation schemes meet the diversion requirements without causing adverse hydraulic interactions.